PENERAPAN METODE PEMBELAJARAN KOOPERATIF SNOWBALL THROWING UNTUK MENINGKATKAN HASIL BELAJAR PENDIDIKAN AGAMA ISLAM DAN BUDI PEKERTI: SEKOLAH DASAR NEGERI SUMBERSUKO 1 (Dewan Pendidikan Bondowoso, 2020)
This study aims to find out how much improvement activity and student learning outcomes PABP (Religious Education and Budi Pekerti) training materials amaul husna through the application of cooperative learning methods snowball throwing class 6 SD Negeri 1 Sumbersuko. This research was conducted in SD Negeri 1 Sumbersuko Klabang, academic year 2018-2019, with the research subjects of grade 6 students as many as 20 students. This study is a type of classroom action research, the learning method used is cooperative learning method of snowball throwing. The study was conducted with 3 cycles. From the results of the study showed increased activity and student learning outcomes. The positive activity of students from each cycle increased from cycle I by 50%; in cycle I of 6.79; on the second cycle of 7.42 and on the third cycle of 8.85. The conclusion of this research is the result of study of 6th grade students at SD Negeri 1 Sumbersuko. can be improved through cooperative learning method learning technique snowball throwing method